Exemplifying the Behaviour of the Prophet Muhammad Saw: An Approach to Islamic Character Education - Hasanbasri; Ellya Roza (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2023)
The Messenger of Allah was present in the world, having several essential tasks, including the first as an educator and the second to provide facilities for the problems faced by friends. The purpose of compiling this work is to find the concept of educating Prophet Muhammad Saw as an example of character education. The author used the preparation of this work with a library research approach. The author uses primary sources to collect data, namely books, journals, and other essential documents related to this work's writing. The analysis used by the author in this preparation is descriptive. The results of this work are 1). The Prophet taught education about simplicity through simple and logical techniques. He uses the discussion and feedback method and provides examples of case studies to make it easier for friends to understand. In addition, the tasywiq process increases motivation and enthusiasm for learning from friends.